On the existence of certain weak Fano threefolds of Picard number two - Arap, Maxim; Cutrone, Joseph; Marshburn, Nicholas (MATHEMATICA SCANDINAVICA, 2017)
This article settles the question of existence of smooth weak Fano threefolds of Picard number two with small anti-canonical map and previously classified numerical invariants obtained by blowing up certain curves on smooth Fano threefolds of Picard number 1 with the exception of 12 numerical cases.